2023
DOI: 10.2196/44104
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Social Cognitive Determinants and Movement-Related Behaviors in Studies Using Ecological Momentary Assessment Methods: Systematic Review

Abstract: Background The social cognitive framework is a long-standing framework within physical activity promotion literature to explain and predict movement-related behaviors. However, applications of the social cognitive framework to explain and predict movement-related behaviors have typically examined the relationships between determinants and behavior across macrotimescales (eg, weeks and months). There is more recent evidence suggesting that movement-related behaviors and their social cognitive determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…Participants complete follow-up assessments at baseline, 2, 4, 6, and 8 weeks after randomization, which include the MoCA, Digit Span Test, QoL, and multiple functional assessments. Additionally, participants are prompted to complete ecological momentary assessments [22] twice weekly throughout the 2-month postrandomization period. The study flow diagram is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Participants complete follow-up assessments at baseline, 2, 4, 6, and 8 weeks after randomization, which include the MoCA, Digit Span Test, QoL, and multiple functional assessments. Additionally, participants are prompted to complete ecological momentary assessments [22] twice weekly throughout the 2-month postrandomization period. The study flow diagram is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the social cognitive theory (18,19) postulates that self-efficacy and outcome expectations impact behavior through goals. This static level of theory does well to describe between-person differences between those who are more or less active (e.g., (20)), but not when applied to within-person assessments of the day-to-day life experiences (21). How can we expect this generic, static representation of theory to describe the complexity of how, or to what extent, a person adjusts to evolving expectations following failed attempts to meet goals, for example?…”
Section: The Value Of Computational Modelsmentioning
confidence: 99%